Influence of menopause on serum lipoprotein (a)[Lp(a)] - Sultana, N; Ahmed, S; Parvin, S; Mahal, M; Chowdhury, NS (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10529 J. Dhaka Med. Coll. 2011; 20(2): 102-106